Australian Transnational Educational Leadership Roles: Challenges, Opportunities and Experiences - Giridharan, Beena; Ling, P.; Mazzolini, M.; Goerke, Veronica (Office of Teaching and Leanring, Curtin University Sarawak, 2013)
The establishment of higher educational hubs in Malaysia and Singapore has spurred the growth of transnational education (TNE) offerings in Asia, and attracted several Australian higher education providers to set up branch campuses in these countries. In Malaysia, TNE is seen as contributing to economic targets by helping to decrease the outflow of students and currency, and by attracting international students to Malaysian shores (British Council 2012). The provision of higher education through TNE raises issues somewhat distinct from those arising with local provision of higher education. These include the balance of local and foreign educational decision making and its implications for academic staff and for the learning experiences of students. This paper is informed by ‘Learning without Borders: Leadership in transnational education and internationalization of curriculum’, an Australian Office of Learning and Teaching (OLT) funded project undertaken at Curtin University and Swinburne University of Technology, involving Australian campuses and branch campuses. The project investigated staff experiences, expectations and preferences on TNE issues including career path opportunities, teaching and learning implications. The project focused particularly on the development of recognition and support for leadership roles in transnational education and on internationalization of curriculum. The paper highlights some of the TNE and internationalization measures that might enhance staff experiences and student learning.